(untitled) (Derna Academy Journal for Applied Sciences, 2026)
Background: Type 2 diabetes mellitus (T2DM) is increasingly recognised as a metabolic disorder with an inflammatory component. Low‑grade chronic inflammation contributes to insulin resistance and the development of diabetic complications. This study aimed to evaluate inflammatory markers in patients with T2DM compared with healthy controls and to assess their relationship with glycemic control. Methods: A case–control study was conducted in Derna City, Libya, including 45 patients with T2DM and 30 healthy controls. Fasting blood sugar (FBS), glycated haemoglobin (HbA1c), white blood cell count (WBC), neutrophil count, lymphocyte count, C‑reactive protein (CRP), and neutrophil‑to‑lymphocyte ratio (NLR) were measured. Statistical analysis was performed using SPSS version 26. Independent‑sample t‑test or Mann–Whitney U test was applied as appropriate. Spearman’s correlation was used to assess associations between inflammatory markers and glycemic parameters. Results: Patients with T2DM showed significantly higher CRP, NLR, and WBC values compared with controls. FBS and HbA1c were markedly elevated in the diabetic group. Spearman analysis revealed a strong positive correlation between FBS and HbA1c (r=0.889, p<0.001). CRP and NLR were moderately correlated with WBC, indicating an inflammatory linkage. However, no significant correlation was observed between glycemic parameters and inflammatory markers . Conclusion: Inflammatory markers such as CRP and NLR are elevated in patients with T2DM, supporting the role of low‑grade inflammation in diabetes. Although direct correlations with glycemic control were not significant, these markers may serve as useful indicators of systemic inflammation in T2DM patients